Translation Techniques and Their Impacts on Translated Verbs in iPhone User Guide - Novitasari, Nine Febrie; Firdaus, Ahmad Yusuf; Safitri, Nadya; Rachman, Alif Fatahilla (Faculty of Tarbiyah and Teacher Training, IAIN Jember, 2025)
This study looks at how verbs are translated from English to Indonesian in the iPhone 13 Pro Max user guide, and how the translation techniques used affect how acceptable the translations are to Indonesian readers. While many studies have looked at translating technical texts, not many have focused on verbs or how they affect users’ understanding. This study fills that gap by focusing on verbs, which are important in user guides because they give instructions that need to be clear and easy to follow. The study uses a qualitative method, applying Molina and Albir’s (2002) framework to identify the translation techniques, and Nababan’s (2012) model to measure how acceptable the translations are. Five Indonesian iPhone users were asked to rate how natural and clear the translated verbs were using a three-point scale. The results show that established equivalent was the most commonly used technique and had the highest acceptability. Other techniques such as linguistic compression, compensation, transposition, and modulation were used less often but were still mostly acceptable. By connecting translation techniques to user feedback, this study offers a focused and user-centered contribution to translation studies. It also gives useful insights for translators and user guide developers who want to make their translations clearer, more culturally appropriate, and easier to understand.